Metabolism heterogeneity in melanoma fuels deactivation of immunotherapy: Predict before protect - Zhang, Xinyue; Tai, Zongguang; Miao, Fengze; Huang, Hao; Zhu, Quangang; Bao, Leilei; Chen, Zhongjian (Frontiers in Oncology, 2022)
Malignant melanoma is widely acknowledged as the most lethal skin malignancy. The metabolic reprogramming in melanoma leads to alterations in glycolysis and oxidative phosphorylation (OXPHOS), forming a hypoxic, glucose-deficient and acidic tumor microenvironment which inhibits the function of immune cells, resulting in a low response rate to immunotherapy. Therefore, improving the tumor microenvironment by regulating the metabolism can be used to improve the efficacy of immunotherapy. However, the tumor microenvironment (TME) and the metabolism of malignant melanoma are highly heterogeneous. Therefore, understanding and predicting how melanoma regulates metabolism is important to improve the local immune microenvironment of the tumor, and metabolism regulators are expected to increase treatment efficacy in combination with immunotherapy. This article reviews the energy metabolism in melanoma and its regulation and prediction, the integration of immunotherapy and metabolism regulators, and provides a comprehensive overview of future research focal points in this field and their potential application in clinical treatment.